2005
DOI: 10.1007/s00330-005-0040-1
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution computed tomography of the lungs: the borderlands of normality

Abstract: High-resolution computed tomography (HRCT) is now widely used in the assessment of airways and diffuse lung disease. Considerable literature on pathologic correlation has increased the understanding of the signs of disease seen on HRCT. However, neither the significance of subtle individual signs nor the spectrum of HRCT appearances in healthy lungs is well documented. HRCT signs that cause diagnostic uncertainty and the spectrum of findings that exist between definite normality and definite abnormality are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…Conversely, the increasing use of HRCT has led to situations in which limited features of ILD are seen in patients in whom the clinical significance is unclear. In some cases these changes may be within the limits of normality 161. It has been reported that approximately one-third of smokers have parenchymal changes such as patchy ground glass opacification and centrilobular nodules without obvious symptomatic or functional correlates 162 163.…”
Section: High Resolution Computed Tomography (Hrct)mentioning
confidence: 99%
“…Conversely, the increasing use of HRCT has led to situations in which limited features of ILD are seen in patients in whom the clinical significance is unclear. In some cases these changes may be within the limits of normality 161. It has been reported that approximately one-third of smokers have parenchymal changes such as patchy ground glass opacification and centrilobular nodules without obvious symptomatic or functional correlates 162 163.…”
Section: High Resolution Computed Tomography (Hrct)mentioning
confidence: 99%
“…52 It has been suggested that air trapping reflects small-airway obstruction by peribronchiolar or intraluminal granulomas. However, it should be stressed that expiratory air trapping is a nonspecific HRCT sign that is not infrequent in healthy subjects 71 ; thus the clinical significance of limited mosaic attenuation is often difficult to interpret.…”
Section: Typical Parenchymal Lesions and Patternsmentioning
confidence: 99%
“…By measuring the lumen area (LA) and wall area (WA) of the bronchi using computed tomography (CT), it is possible to assess the airways function and structure [1][2][3]. These measurements allow a non-invasive monitoring of asthma [4], complementary to clinical and functional tests.…”
Section: Introductionmentioning
confidence: 99%